Defects in ferroelectric HfO2. Issue 27 (30th June 2021) - Chouprik, Anastasia; Negrov, Dmitrii; Tsymbal, Evgeny Y.; Zenkevich, Andrei
Abstract : Following introduction to defects in classical ferroelectrics as well as in dielectric HfO2, this review covers recent experimental results on the impact of defects in ferroelectric HfO2 on its functional properties and resulting performance of memory devices. Abstract : The discovery of ferroelectricity in polycrystalline thin films of doped HfO2 has reignited the expectations of developing competitive ferroelectric non-volatile memory devices. To date, it is widely accepted that the performance of HfO2 -based ferroelectric devices during their life cycle is critically dependent on the presence of point defects as well as structural phase polymorphism, which mainly originates from defects either. The purpose of this review article is to overview the impact of defects in ferroelectric HfO2 on its functional properties and the resulting performance of memory devices. Starting from the brief summary of defects in classical perovskite ferroelectrics, we then introduce the known types of point defects in dielectric HfO2 thin films. Further, we discuss main analytical techniques used to characterize the concentration and distribution of defects in doped ferroelectric HfO2 thin films as well as at their interfaces with electrodes. The main part of the review is devoted to the recent experimental studies reporting the impact of defects in ferroelectric HfO2 structures on the performance of different memory devices. We end up with the summary and perspectives of HfO2 -based ferroelectric competitive non-volatile memory devices.